Relations between patient and staff member characteristics and staff member injury on a psychiatric inpatient unit for children with intellectual or developmental disabilities. Issue 3 (23rd July 2020) - Romani, Patrick W.; Ariefdjohan, Merlin; Jensen Gaffey, Lyndsay L.; Torres‐Dominguez, Maria; Lister, Jada
Abstract: Problem: Staff member injuries are a pervasive and long‐standing problem for psychiatric inpatient units. Method: The current study analyzed the prevalence of staff member injury and characteristics of patients that injured staff on a specialized psychiatric unit for children with intellectual or developmental disabilities. We evaluated staffing patterns as well as characteristics of patients (e.g., diagnoses, body mass index) between 2016 and 2018. This time period was selected because it represented an approximately equal period before and after the introduction of a new clinical model that incorporated applied behavior analysis (ABA) and other safety‐related practices (e.g., personal protective equipment). Findings: During this study period, there were 110 cases of staff injuries caused by 42 patients. Injuries were most likely to occur during physical management of a patient engaging in aggressive behavior, but less so when strategies requiring less physical contact were implemented. The frequency of staff injury was also significantly related to patients' diagnoses, particularly those exhibiting aggressive behavior and diagnosed with moderate‐to‐severe intellectual disability and/or autism spectrum disorder. Conclusions: Robust staff training incorporating the principles of ABA and the provision of other safety‐related resources can be integrated to clinical guidelines to promote the safety of staff practicing in psychiatric inpatient units.